2013
DOI: 10.1002/j.1556-6676.2013.00118.x
|View full text |Cite
|
Sign up to set email alerts
|

Support and Barriers for Latino Male Students' Educational Pursuits: Perceptions of Counselors and Administrators

Abstract: Counselors and secondary/postsecondary administrators (N= 14) were interviewed to explore their perceptions of barriers and resources related to Latino male students' postsecondary goals and pursuit of higher education. Issues examined included the lack of awareness of educational obstacles for Latino male students by educators, role of Latino male students' families in the students' educational experiences, impact of peers and mentoring on Latino male students, and the role of program outreach and partnership… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
48
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(49 citation statements)
references
References 40 publications
1
48
0
Order By: Relevance
“…In a study involving Latina/o college students, J. Cavazos et al () found that family support was integral to components of personal resilience. This finding is similar to Clark, Ponjuan, Orrock, Wilson, and Flores's () finding that counselors and administrators identified Hispanic families' high expectations and value on education as critical to students' educational experiences. Finally, Edwards and Lopez () found that family support influenced Mexican American adolescents' perceptions of life satisfaction.…”
Section: Family Importancesupporting
confidence: 86%
“…In a study involving Latina/o college students, J. Cavazos et al () found that family support was integral to components of personal resilience. This finding is similar to Clark, Ponjuan, Orrock, Wilson, and Flores's () finding that counselors and administrators identified Hispanic families' high expectations and value on education as critical to students' educational experiences. Finally, Edwards and Lopez () found that family support influenced Mexican American adolescents' perceptions of life satisfaction.…”
Section: Family Importancesupporting
confidence: 86%
“…Hence, Latina/o students are at greater disadvantage regarding access to social and cultural capital than their U.S. born, European American, and Asian peers (Contreras, 2005;García, 2012;Medina & Posadas, 2012). Mentoring relationships can provide Latina/o students with the support necessary to overcome barriers to higher educational attainment (Clark et al, 2013;Medina & Posadas, 2012). Hon and Shorr (1997), in a quantitative study, examined mentoring of Latina/o youth and the positive impact these relationships can have on their academic success.…”
Section: Latina/o Youth As First-generation College Studentsmentioning
confidence: 96%
“…The Latina/os who do go on to pursue a college education are faced with many barriers due to factors such as cultural expectations and their underrepresentation in college campuses (Clark et al, 2013). In many cases, Latina/os enrolled in higher education find themselves being the "lonely onlys" in their classes -the only Latina/o, or even at times the only ethnic minority -who are called upon frequently to give the "minority perspective" (Castellanos & Gloria, 2007).…”
Section: Latina/o Youth As First-generation College Studentsmentioning
confidence: 99%
See 1 more Smart Citation
“…L. Rodriguez, 2002), and socio-economic level (e.g., Barrett, Barile, Malm, & Weaver, 2012;Clark, Ponjuan, Orrock, Wilson, & Flores, 2013;O'Connor, 2009). Moreover, with the exception of a few studies (e.g., Goldenberg, Gallimore, Reese, & Garnier, 2001), research findings to date have shown that academic success among Latina/o students is positively related to socio-cultural variables such as parental education levels (e.g., Hannon, 2015;Plunkett & Bámaca-Gómez, 2003;Plunkett, Behnke, Sands, & Choi, 2009).…”
Section: Theoretical Framework and Related Literaturementioning
confidence: 96%